2014
DOI: 10.3390/ijms150610398
|View full text |Cite
|
Sign up to set email alerts
|

The Metallothionein Gene, TaMT3, from Tamarix androssowii Confers Cd2+ Tolerance in Tobacco

Abstract: Cadmium (Cd) is a nonessential microelement and low concentration Cd2+ has strong toxicity to plant growth. Plant metallothioneins, a class of low molecular, cystein(Cys)-rich and heavy-metal binding proteins, play an important role in both metal chaperoning and scavenging of reactive oxygen species (ROS) with their large number of cysteine residues and therefore, protect plants from oxidative damage. In this study, a metallothionein gene, TaMT3, isolated from Tamarix androssowii was transformed into tobacco (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In addition to chelating extra metal ions in plant cells via their Cys thiol groups, MTs may also enhance plant tolerance to stress by up-regulating anti-oxidative enzymes to maintain the redox balance and thereby reduce ROS-induced injury [ 15 , 17 , 37 , 38 ]. To make clear the role of ricMT on oxidative damage, rice suspension cells of sense- and antisense- ricMT transgenic lines were obtained by an Agrobacterium -mediated transformation for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to chelating extra metal ions in plant cells via their Cys thiol groups, MTs may also enhance plant tolerance to stress by up-regulating anti-oxidative enzymes to maintain the redox balance and thereby reduce ROS-induced injury [ 15 , 17 , 37 , 38 ]. To make clear the role of ricMT on oxidative damage, rice suspension cells of sense- and antisense- ricMT transgenic lines were obtained by an Agrobacterium -mediated transformation for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al [ 196 ] showed that expression of Elsholtzia haichowensis metallothionein type 1 ( EhMT1 ) in tobacco plants not only increased the tolerance of transgenic tobacco to copper toxicity but also decreased the synthesis of hydrogen peroxide and improved peroxidase activity (POD) in roots, leading to enhanced ability of plants to cope with oxidative stress. Zhou et al [ 9 ] demonstrated that although TaMT3 , a metallothionein type 3 from Tamarix androssowii , engineered into tobacco resulted in increased tolerance to Cd stress through significant increases of SOD functionality, which raised the ability of ROS cleaning-up in transgenic plant, it led to decreased POD activity. It seems that the impact of the expressed metallothionein on distinct components of antioxidant system of transgenic plants is different, which requires further investigation.…”
Section: Some Defense Mechanisms Employed By Plants Against Hm Strmentioning
confidence: 99%
“…HMs belong to group of nonbiodegradable, persistent inorganic chemical constituents with the atomic mass over 20 and the density higher than 5 g·cm −3 that have cytotoxic, genotoxic, and mutagenic effects on humans or animals and plants through influencing and tainting food chains, soil, irrigation or potable water, aquifers, and surrounding atmosphere [ 3 – 6 ]. There are two kinds of metals found in soils, which are referred to as essential micronutrients for normal plant growth (Fe, Mn, Zn, Cu, Mg, Mo, and Ni) and nonessential elements with unknown biological and physiological function (Cd, Sb, Cr, Pb, As, Co, Ag, Se, and Hg) [ 5 , 7 9 ]. Both underground and aboveground surfaces of plants are able to receive HMs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MTs are a class of low-molecular (6–7 kDa) cysteine (Cys)-rich proteins that bind heavy metals [ 8 , 9 ], and were first reported as a cadmium binding protein in the cortex of horse kidney [ 10 ]. This protein not only has effects on detoxification of heavy metals like cadmium and mercury [ 11 ], regulation of the homeostasis of essential metals including zinc and copper [ 12 , 13 ], but also has functions like protecting reactive oxygen species [ 14 , 15 ] and DNA damage [ 16 ], in animals, plants and microorganisms. A large number of cysteine residues in MTs are able to bind a variety of metals by the formation of mercaptide bonds [ 17 ].…”
Section: Introductionmentioning
confidence: 99%